Validation of the Thai Version of the Movement Disorder Society-Sponsored Revision of the Unified Parkinson's Disease Rating Scale - Priya Jagota; Prachaya Srivanitchapoom; Sitthi Petchrutchatachart; Surat Singmaneesakulchai; Apichart Pisarnpong; Praween Lolekha; Suwanna Setthawatcharawanich; Parnsiri Chairangsaris; Natlada Limotai; Pawut Mekawichai; Pattamon Panyakaew; Onanong Phokaewvarangkul; et al. (Journal of Movement Disorders, 2022)
Objective This study aims to validate the Thai translation of the Movement Disorder Society-sponsored revision of the Unified Parkinson’s Disease Rating Scale (MDS-UPDRS). Methods The English version was translated into Thai and then back-translated into English. The translated version underwent 2 rounds of cognitive pretesting to assess the ease of comprehension, ease of use and comfort with the scale. Then, it underwent large clinimetric testing. Results The Thai version was validated in 354 PD patients. The comparative fit index (CFI) for all four parts of the Thai version of the MDS-UPDRS was 0.93 or greater. Exploratory factor analysis identified isolated item differences in factor structure between the Thai and English versions. Conclusion The overall factor structure of the Thai version was consistent with that of the English version based on the high CFIs (all CFI ≥ 0.90). Hence, it can be designated the official Thai version of the MDS-UPDRS.